Pengaruh Lingkungan Kerja, Motivasi, dan Disiplin Kerja Terhadap Kinerja Pegawai di Puskesmas Sapat Kabupaten Indragiri Hilir - Herdian Herdian; Kamali Zaman (Universitas Batanghari Jambi, 2023)
Based on an initial survey of 5 employees at the Sapat Health Center, 3 employees said that the employee's performance was not optimal, such as work motivation was lacking, namely the absence of rewards and punishments. Many employees who work complain because the room conditions are not possible, if you look at it from a geographical point of view the mileage uses sea transportation and takes a long time on the way. Meanwhile, observations from TU employees about discipline there are some employees who often do not come to the office. The purpose of this study is to analyze the evaluation of information about the Influence of the Work Environment, Motivation, and Work Discipline on Employee Performance at the Sapat Health Center. Research location at Puskesmas Sapat, Indragiri Hilir Regency. The research location is at the Sapat Health Center, Indragiri Hilir Regency. A type of quantitative analytical research, using a cross-sectional research design. The study sample had 37 samples. Data collection is carried out by distributing questionnaires. The results showed that the results of the relationship closeness analysis obtained a Prevalent Odds Ratio (POR) of 5,600, respondents with an unfavorable work environment had a risk of 5.6 times performing poorly. The results of the relationship closeness analysis obtained a Prevalent Odds Ratio (POR) of 6.875, respondents whose work motivation was not good had a risk of 6.8 times performing poorly. The results of the relationship closeness analysis obtained a Prevalent Odds Ratio (POR) of 7,500, respondents who were not good work discipline had a risk of 7.5 times performing poorly. There is a simultaneous influence between work environment, motivation, and work discipline on performance (Fhitung > Ftabel). There is an influence of Work Environment, Motivation, and Work Discipline on Employee Performance and the simultaneous relationship between the work environment, motivation, and work discipline on performance